A New Record of the Genus Onthophagus Latreille, 1802 (Coleoptera: Scarabaeidae) from Northern Western Ghats, Maharashtra, India - Jagdale, Pranil; Magdum, Sujata; Kalawate, Aparna Sureshchandra (Journal of the Bombay Natural History Society (JBNHS), 2023)
No Abstract.